Using the Implicit Association Test to Assess Risk Propensity Self‐concept: Analysis of its Predictive Validity on a Risk‐taking Behaviour in a Natural Setting. Issue 5 (11th July 2013) - Horcajo, Javier; Rubio, Víctor J.; Aguado, David; Hernández, José Manuel; Márquez, M. Oliva
Abstract The present work analyses the predictive validity of measures provided by several available self‐report and indirect measurement instruments to assess risk propensity (RP) and proposes a measurement instrument using the Implicit Association Test: the IAT of Risk Propensity Self‐Concept (IAT‐RPSC), an adaptation of the prior IAT‐RP of Dislich et al. Study 1 analysed the relationship between IAT‐RPSC scores and several RP self‐report measures. Participants' risk‐taking behaviour in a natural setting was also assessed, analyzing the predictive validity of the IAT‐RPSC scores on risk‐taking behaviour compared with the self‐report measures. Study 2 analysed the predictive validity of the IAT‐RPSC scores in comparison with other indirect measures. Results of these studies showed that the IAT‐RPSC scores exhibited good reliability and were positively correlated to several self‐report and indirect measures, providing evidence for convergent validity. Most importantly, the IAT‐RPSC scores predicted risk‐taking behaviour in a natural setting with real consequences above and beyond all other self‐report and indirect measures analysed. Copyright © 2013 European Association of Personality Psychology